The issue of security in the elections programmes of candidates for the office of President of Ukraine in 2019 - Pietnoczka, Paweł (Przegląd Wschodnioeuropejski, 2023)
The aim of the article is to present the programme priorities in the field of security policy, announced by each candidate running for the office of President of Ukraine in 2019. In addition, it also attempts to show how they intended to: ensure state security, bring the war in the Donbass to an end, restore the territorial integrity – thus, to regain Kyiv’s control over the Donbass and Crimea, as well as where they were going to look for allies capable of providing support to Ukraine on the path to achieving the above-mentioned goals. An analysis of the elections programmes of each candidate will allow us to answer the questions. Attention was paid to the programme demands of those candidates who reeived at least a five per cent support in the presidential elections. Hence, the elections programmes of the participants of the second round of the elections, namely those of Volodymyr Zelensky, Petro Poroshenko, and also Yulia Tymoshenko, Yuriy Boyko, Anatoliy Hrytsenko, Ihor Smeshko as well as Oleh Lyashko, were subjected to analysis.